(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article presents the results of studies devoted to water-saving irrigation technology on steep slopes and clarifies the elements of irrigation technology for contour irrigation in the conditions of southern Uzbekistan.